Care self-efficacy in adolescents with mental disorders: A qualitative study - Soudabeh Behzadi; Shahrzad Yektatalab; Marzieh Momennasab; Maryam Shaygan; Armin Zareiyan (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The promotion of health in adolescents with mental disorders depends on their levels of self-care empowerment. Self-efficacy is a significant prerequisite for successful self-management and behavior change in adolescents with mental disorders. The present study was conducted to explain the concept of care self-efficacy in adolescents with mental disorders. MATERIALS AND METHODS: This qualitative study was carried out using the conventional content analysis approach. Semi-structured interviews (n = 34) were conducted with adolescents having mental disorders, their families, and healthcare providers. The participants were selected from neurology and psychiatry clinics affiliated with University of Medical Sciences using the purposeful sampling method in 2021. Data were analyzed according to Graneheim and Lundman method. RESULTS: According to the findings of content analysis, four main themes were derived from the data: "health information-seeking behavior," "adaptation of life to the disease and treatment conditions," "adaptive coping," and "social self-care." CONCLUSION: Based on the findings, the promotion of adaptive styles and social support is effective in acquiring social competencies. As a result, policymakers are suggested to design health-oriented educational programs based on care self-efficacy principles to promote health in adolescents with mental disorders.